The Tale of the Dueling Neurosurgeons. A Contribution to the Neurosciences and Neurosurgery - da Silva, Gilvan Aguiar; da Silva, Elton Gomes; López, Seidel Guerra (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
In the present article, we elaborate a critical review of the book “The Tale of the Dueling Neurosurgeons: The History of the Human Brain as Revealed by True Stories of Trauma, Madness, and Recovery”, written by Sam Kean. In our opinion, this book can contribute to the dissemination of neurosciences to the lay public, but it can also have an important role: to increase the interest of medicine students in neurosciences and research, since an increasingly lower number of students declare they have this interest. Thus, this book can be an important tool to deal with a pertinent and current issue under debate in the neuroscience research and neurosurgery communities.
Keywords: neuroscience; career in neurosurgery; medicine; medical education; career in research